2018
DOI: 10.3389/fneur.2018.00254
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Trigger Point Manual Treatment on the Frequency, Intensity, and Duration of Attacks in Primary Headaches: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundA variety of interventions has been proposed for symptomatology relief in primary headaches. Among these, manual trigger points (TrPs) treatment gains popularity, but its effects have not been investigated yet.ObjectiveThe aim was to establish the effectiveness of manual TrP compared to minimal active or no active interventions in terms of frequency, intensity, and duration of attacks in adult people with primary headaches.MethodsWe searched MEDLINE, COCHRANE, Web Of Science, and PEDro databases up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 91 publications
2
20
0
1
Order By: Relevance
“…Therefore, it is possible that clinical presentation of muscle TrPs could be slightly different between women and men with TTH, and hence, careful clinical examination should be conducted. Second, a recent meta‐analysis provided preliminary evidence suggesting that manual treatment of active TrPs may be effective for TTH; however, the quality of evidence was still low because of the presence of few studies and the imprecision of results . It is possible that the results of our study provide a potential explanation for discrepancies in the effects of TrP treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, it is possible that clinical presentation of muscle TrPs could be slightly different between women and men with TTH, and hence, careful clinical examination should be conducted. Second, a recent meta‐analysis provided preliminary evidence suggesting that manual treatment of active TrPs may be effective for TTH; however, the quality of evidence was still low because of the presence of few studies and the imprecision of results . It is possible that the results of our study provide a potential explanation for discrepancies in the effects of TrP treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Among various manual treatments for MFP associated with MTrPs, the most commonly used are compression technique, myofascial release, acupressure, muscle energy technique, and specific soft tissue mobilization techniques [14]. However, manual treatments for MTrPs have varying degrees of effectiveness and it is hard to identify the most effective rehabilitation method for MTrPs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the manual treatments for MTrPs and MFP, the compression technique (CT), myofascial release, acupressure, muscle energy technique, and specific soft tissue mobilization techniques are most often used. A systematic review and meta-analysis of randomized controlled trials reported that manual MTrPs treatment of head and neck muscles may reduce the frequency, intensity, and duration of tension-type headache, but the quality of evidence was very low [14]. Moreover, it is currently impossible to identify the most effective treatment technique for MTrPs among those proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Постизометрическая релаксация применяется у пациентов с мигренью и сочетанным выраженным перикраниальным мышечно-тоническим синдромом [108]. Метод направлен на расслабление перикраниальных мышц, упражнения включают два этапа -сокращение и расслабление напряженных мышц.…”
Section: немедикаментозное лечениеunclassified